Advances in next-generation sequencing for relapsed pediatric acute lymphoblastic leukemia: current insights and future directions - Mohd Nippah, Nur Farhana; Abu, Nadiah; Ab Mutalib, Nurul Syakima; Alias, Hamidah (Frontiers in Genetics, 2024)
Leukemia is one of the most common cancers in children; and its genetic diversity in the landscape of acute lymphoblastic leukemia (ALL) is important for diagnosis, risk assessment, and therapeutic approaches. Relapsed ALL remains the leading cause of cancer deaths among children. Almost 20% of children who are treated for ALL and achieve complete remission experience disease recurrence. Relapsed ALL has a poor prognosis, and relapses are more likely to have mutations that affect signaling pathways, chromatin patterning, tumor suppression, and nucleoside metabolism. The identification of ALL subtypes has been based on genomic alterations for several decades, using the molecular landscape at relapse and its clinical significance. Next-generation sequencing (NGS), also known as massive parallel sequencing, is a high-throughput, quick, accurate, and sensitive method to examine the molecular landscape of cancer. This has undoubtedly transformed the study of relapsed ALL. The implementation of NGS has improved ALL genomic analysis, resulting in the recent identification of various novel molecular entities and a deeper understanding of existing ones. Thus, this review aimed to consolidate and critically evaluate the most current information on relapsed pediatric ALL provided by NGS technology. In this phase of targeted therapy and personalized medicine, identifying the capabilities, benefits, and drawbacks of NGS will be essential for healthcare professionals and researchers offering genome-driven care. This would contribute to precision medicine to treat these patients and help improve their overall survival and quality of life.